Ferroptosis: a new strategy for Chinese herbal medicine treatment of diabetic nephropathy - Wei, Maoying; Liu, Xingxing; Tan, Zhijuan; Tian, Xiaochan; Li, Mingdi; Wei, Junping (Frontiers in Endocrinology, 2023)
Diabetic nephropathy (DN) is a serious microvascular complication of diabetes. It has become a leading cause of death in patients with diabetes and end-stage renal disease. Ferroptosis is a newly discovered pattern of programmed cell death. Its main manifestation is the excessive accumulation of intracellular iron ion-dependent lipid peroxides. Recent studies have shown that ferroptosis is an important driving factor in the onset and development of DN. Ferroptosis is closely associated with renal intrinsic cell (including renal tubular epithelial cells, podocytes, and mesangial cells) damage in diabetes. Chinese herbal medicine is widely used in the treatment of DN, with a long history and definite curative effect. Accumulating evidence suggests that Chinese herbal medicine can modulate ferroptosis in renal intrinsic cells and show great potential for improving DN. In this review, we outline the key regulators and pathways of ferroptosis in DN and summarize the herbs, mainly monomers and extracts, that target the inhibition of ferroptosis.